Digital-Based Expedition Planning to Improve Operational Efficiency - Ulfa Maslahah; Kusumayasa, Ghaluh; Albart, Nicko (Research Horizon, 2025)
Digital transformation has become a key factor in improving the operational efficiency of the shipping industry amid the growth of global e-commerce and changing consumer behavior. This research focuses on the development of a digital-based expedition business planning model that integrates technologies such as Enterprise Resource Planning (ERP), Internet of Things (IoT), and big data analytics. This study uses a descriptive qualitative approach to explore the impact of digitalization adoption on cost reduction, delivery acceleration, and improvement of customer service quality. The results show that operational digitalization is able to overcome traditional inefficiencies, speed up workflows, and improve accuracy and speed of services. However, the implementation of digitalization also faces challenges, including the need for changes in organizational culture, human resource readiness, and cybersecurity risks. With proper strategic planning, digitalization can be a key catalyst in strengthening the competitiveness of expedition companies, especially in the small and medium-sized segments. These findings make a theoretical and applicable contribution to the development of digital transformation strategies in the modern logistics industry.